Is quality still free?: Empirical evidence on quality cost in modern manufacturing - Plewa, Markus; Kaiser, Gernot; Hartmann, Evi (International Journal of Quality and Reliability Management, 2016)
Purpose The purpose of this paper is to provide empirical evidence for competing representations of the prevention-appraisal-failure model of quality cost. Design/methodology/approach The authors conduct regression analysis on a secondary data set to reveal relationships among total cost of quality, its components and overall quality performance. Findings Total cost of quality and its failure cost component are significantly lower at higher levels of quality, while the prevention and appraisal cost components are not observed to be significantly higher at higher levels of quality. The authors propose a modification to the modern representation of the prevention-appraisal-failure model. Practical implications In manufacturing, ever higher levels of quality are associated with significantly lower quality cost. Originality/value Using a large, unique data set for secondary analysis, combined with employing a high-level measure for overall quality performance, the authors provide evidence for the aggregate explanatory power of prevalent representations of the prevention-appraisal-failure cost of quality mode
Keywords: Manufacturing; Quality management; Quality costs; Secondary data analysis

Long-run dynamics between product life cycle length and innovation performance in manufacturing - Plewa, Markus (Managing Innovation: What Do We Know About Innovation Success Factors?, 2019)
Changes in the duration of product life cycles (PLCs) have been identified as a driving factor for increasing the speed of new product development (NPD). However, the facilitating potential of increasing the speed to market of new products regarding their success has been subject to extensive debate. In this paper, we shed light on the long-run dynamics between PLC and key innovation performance indicators. A large secondary data set allows us to investigate long-run within-company differences. We observe significantly shrinking PLC on the one hand and significantly increasing NPD speed on the other. A change in the length of the PLC is positively linked to changes in time to market (Ttmarket) and time to volume. Also, we confirm a positive empirical relationship between shorter Ttmarket and quicker implementation of targeted quality and productivity. However, we cannot confirm a positive relationship between shorter Ttmarket and shorter time to break-even of investments.
CRIS-Team Scopus Importer:2019-07-30
Keywords: break-even point; innovation speed; manufacturing; New product development; new product success; NPD; PLC; product life cycle; secondary data; time to market

Quality is free – New Empirical Evidence from Manufacturing - Plewa, Markus; Kaiser, Gernot; Hartmann, Evi; Feisel, Edda (Academy of Management Journal, 2015)
We provide new empirical evidence for competing representations of the prevention-appraisal-failure model of quality cost. Using a large, unique data set for secondary analysis, combined with employing a high-level measure for overall quality performance, we validate the aggregate explanatory power of the prevalent cost of quality model variants. We conduct regression analysis to reveal relationships among total cost of quality, its components and overall quality performance. As a result, total cost of quality and its failure cost component are observed significantly lower at higher levels of quality, while the prevention and appraisal cost components are not observed to be significantly higher at higher levels of quality. Consequently we propose a modification to the modern representation of the prevention-appraisal-failure model to explain the data consistently. The important management implication is that in manufacturing, ever higher levels of quality are associated with significantly lower quality cos
Keywords: Manufacturing; Quality; Management; Secondary; Data; Analysis

Trade credit, cost of capital and the role of buyer market power from an agency-theory perspective - Liebl, John; Plewa, Markus; Hartmann, Evi (DSI Annual Meeting 2016, 2016)